Pengaruh Penggunaan Media Pembelajaran Panlintarmatika terhadap Hasil Belajar Siswa pada Mata Pelajaran Matematika di SD - Rizka Anggilia; Misdalina Misdalina; Tanzimah Tanzimah (Journal on Education, 2023)
This study aims to determine the influence of panlintarmatics learning media on student learning outcomes in mathematics subjects in elementary schools. The research method used is quantitative type of experiment with the form of true experimental design and posttest only control design. The sample in this study amounted to 45 students consisting of class 3 A as an experimental class totaling 25 students and class 3 B as a control class totaling 20 students The data collection techniques used were tests and documentation. The data analysis technique used is the t test (independent sample t test). From the results of research data processing with the help of the SPSS application, a value of tcount = 4.825 and a value of ttable = 1.681 with α = 0.05 and df = 43, then 4.825 ≥ 1.681 thus tcount ≥ ttable. In accordance with the criteria for hypothesis testing, H0 rejected and Ha accepted. This shows that there is an influence of panlintarmatics learning media on student learning outcomes in mathematics subjects in elementary schools.